Widespread dissemination of Salmonella, Escherichia coli and Campylobacter resistant to medically important antimicrobials in the poultry production continuum in Canada - Hiddecel Medrano; Sarah Hill; Martine Boulianne; Teresa Cereno; Anne E. Deckert; Audrey Charlebois; Sheryl P. Gow; Kathryn McDonald; Richard J. Reid-Smith; Agnes Agunos (PLoS ONE, 2025)
The Canadian Integrated Program for Antimicrobial Resistance Surveillance (CIPARS) monitors Escherichia coli, Salmonella and Campylobacter and their resistance to antimicrobials in broiler chickens at the farm and slaughter plant levels. In response to many years of CIPARS’ observations and farmers’ data, the Chicken Farmers of Canada implemented a strategy to reduce antimicrobial use in 2014. As resistance genes can be transmitted vertically from parents to their offspring, a study was conducted in broiler breeder flocks to assess the frequency of target bacteria, their antimicrobial resistance (AMR) and to obtain a comprehensive picture of AMR in poultry production. Spent breeder flocks slaughtered between 2018 and 2021 were sampled and data from broiler flocks at the farm and slaughter plants were assessed. Salmonella was most frequently detected in farm broiler chickens (46%), while Campylobacter was most frequently detected in broiler breeders (73%). In Campylobacter, high levels (20–24%) of ciprofloxacin resistance were found across the three production stages, and was highest in farm broiler chickens (24%). In E. coli, an indicator organism, low-level ceftriaxone resistance and occasional isolates that were non-susceptible to ciprofloxacin were noted. Using the indicator, fully susceptible E. coli, broiler breeders had the highest frequency (54%) compared to farm (36%) and slaughtered (35%) broiler chickens. In Salmonella broiler breeders had the highest resistance to most antimicrobials tested.Fully susceptible Salmonella was lowest in broiler breeders (16%) compared to farm (42%) and slaughtered (42%) broiler chickens. Salmonella serovars differed between the production stages, but S. Kentucky was the most predominant. Resistance to critically important antimicrobials in human medicine and regional variations in resistance profiles were observed. This study suggests that broiler breeders carry foodborne bacteria resistant to antimicrobials used in human medicine, demonstrating their role in the maintenance of AMR in poultry and the need to adopt a harmonized sector-wide AMU strategy.